The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/j.1556-6978.2002.tb01300.x
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Process of Clinical Supervisors in Training: An Investigation of the Supervisor Complexity Model

Abstract: The authors investigated C. E. Watkins's (1994) supervisor complexity model (SCM). The Psychotherapy Supervisor Development Scale (PSDS; C. E. Watkins, L. J. Schneider, J. Haynes, & R. Nieberding, 1995) was used to ascertain development over a 15‐week supervision practicum for 12 doctoral students and to compare their development with 7 doctoral students who had not yet begun their practicums. A set of retrospective interview questions produced responses that were used to investigate the viability of the 4 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 11 publications
3
56
0
1
Order By: Relevance
“…One previous study in counseling psychology found that doctoral students in a supervision practicum that included both didactic and experiential components had higher PSDS scores in the middle of and at the end of this training (Baker et al 2002). Further, they suggested that the PSDS is a reliable tool for measuring the impact of supervision training modalities on supervisor development.…”
Section: Purpose Of the Studymentioning
confidence: 94%
“…One previous study in counseling psychology found that doctoral students in a supervision practicum that included both didactic and experiential components had higher PSDS scores in the middle of and at the end of this training (Baker et al 2002). Further, they suggested that the PSDS is a reliable tool for measuring the impact of supervision training modalities on supervisor development.…”
Section: Purpose Of the Studymentioning
confidence: 94%
“…Specifically, training that combines both didactic and experiential components and where the practical training involves the supervision of supervision appears to generate a more significant impact on the supervisor's professional development and practice (Baker, Exum, & Tyler, 2002;Borders, 1996;Gosselin et al, in press;Haley, 2002;Lyon, Heppler, Leavitt, & Fisher, 2008;McMahon & Simons, 2004;Vidlak, 2002). Second, it appears that the key number of training experiences, that is the minimum amount of training that is necessary to produce any discernible change in professional practice, averages between two to three consecutive training opportunities.…”
Section: Research On Clinical Supervision: How Can Someone Become An mentioning
confidence: 94%
“…Furthermore, a future study that included supervisee/supervisor interviews and focus groups would complement and provide more insight into the findings reported in the current study. A future comparative study could investigate perceived self-efficacy of doctoral student supervisors and their supervisees, taking into consideration the developmental levels of both the supervisor trainee and supervisee trainee (Baker et al, 2002;Watkins, 1993). Future research could study the supervisory styles of doctoral student supervisors as they move through their development as supervisors.…”
Section: Recommendations For Future Researchmentioning
confidence: 95%
“…In addition, although the supervision of master's students by doctoral students is customary in counseling programs that offer doctoral degrees, there is scant research pertaining to the supervision practices of doctoral students such as the level of satisfaction and perceived self-efficacy of their supervisees. Baker, Exum, and Tyler (2002) compared 12 doctoral students' development as supervisors over a 15-week practicum with 7 other doctoral students who had not yet begun their practicum. Using responses to interview questions, Baker and colleagues examined the viability of the four proposed developmental stages of the Watkins (1993) Supervisor Complexity Model (SCM).…”
Section: Introductionmentioning
confidence: 99%